ANALISIS PENGARUH KREDIT MACET DAN KECUKUPAN LIKUIDITAS TERHADAP EFISIENSI BIAYA OPERASIONAL BANK UMUM SYARIAH DI INDONESIA - Taudlikhul Afkar (UII, 2017)
ABSTRACTExpense efficiency is one of the ways to gain a bigger profit. Profit, as a component of financial performance measures, indicates the management capability in handling finance issues, such as operational expenses. This study discusses the operational expenses efficiencies related to bad credit or financing problems and liquidity adequacy. The results of this study show that Non Performing Financing (NPF) significantly affects the operational cost efficiency of Islamic Banks in Indonesia as much as 40.2%. It means that in the event of Non Performing Financing (NPF), operational expenses is expected to be inefficient because a significant part of the expenses would be allocated for backup or to erase productive assets collectability. Meanwhile, the liquidity adequacy does not significantly affect the efficiency of the operational expenses. Simultaneously, both of these variables have an important role in the financial performance since they give an overview of their role in the operating expenses efficiency by 20.8%.